Resposta de macrófagos murinos à infecção por Toxoplasma gondii sob a influência de frações hidrofóbicas do parasito e de Serjania lethalis - Napolitano, Danielle Reis (2005)
Macrophages play an important role in defense against infectious agents, during innate or adaptive immunity. They are activated by different microbial components and release cytokines and nitric oxide (NO), an important microbicidal agent. However, these cells also act as hosts for Toxoplasma gondii, which adapted efficient strategies for intracellular survival. In the present study, membrane compounds from T. gondii were extracted and used to evaluate macrophage response to the parasite. Treatment of these cells with hydrophobic fractions from tachyzoites of T. gondii stimulated differently NO production in J774 cells and in peritoneal macrophages from C57BL/6 e BALB/c mice. In addition, macrophages were infected with tachyzoites from T. gondii, after in vitro treatment with fractions and with an extract from Serjania Iethalis, which presents anti-inﬂammatory property. Also, the percentage of infected macrophages from BALB/c was the highest among all other studied cells, and diminished by treatment with FO fraction. Treatment with the extract of S. lethalis decreased NO production by LPS+IFN-y—activated cells and inhibited infection by T. gondii. Our results show at first, that macrophages from mice from different genetic background present different susceptibility of infection by this parasite. Second, the extraction of highly hydrophobic compounds from tachyzoites of T. gondii can yield samples enriched with bioactive molecules that are capable to interfere on parasite—host cell interaction. Finally, NO release by activated macrophages can be regulated in order to prevent damages caused by an intense inﬂammatory response.